1975
DOI: 10.1111/j.1468-2958.1975.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

TOWARD A MESSAGE-CENTERED THEORY OF PERSUASION: THREE EMPIRICAL INVESTIGATIONS OF LANGUAGE INTENSITY1

Abstract: Based on accumulated knowledge concerning the effects of language intensity on attitude change, a set of propositions were advanced that provide a skeletal theoretical framework. Based on the propositions, three separate studies were done to extend the predictive power of the formulation. Predicted interactions between sex of the source, situational anxiety, source credibility, and language intensity were obtained. There were also significant person perception changes as a result of the level of language inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 31 publications
6
78
1
Order By: Relevance
“…The research by Burgoon et al (1974) is only one of many studies that have found that women, in general, are considered to be less credible communicators than males by both males and females in this culture. According to expectancy theory, less credible communicators have a restricted bandwidth, and the use of aggressive message strategies is nonnormative -clearly a negative violation of expectations.…”
Section: Derivation Of Hypotheses and Research Questionsmentioning
confidence: 97%
“…The research by Burgoon et al (1974) is only one of many studies that have found that women, in general, are considered to be less credible communicators than males by both males and females in this culture. According to expectancy theory, less credible communicators have a restricted bandwidth, and the use of aggressive message strategies is nonnormative -clearly a negative violation of expectations.…”
Section: Derivation Of Hypotheses and Research Questionsmentioning
confidence: 97%
“…To date, most language intensity research has tended to be experimental in nature and to focus on the impact of message intensity on impression formation processes within a compliance-gaining context (e.g., Bradac, Bowers, & Courtright, 1979;Burgoon, Jones, & Stewart, 1971;Hamilton & Stewart, 1993;Miller, Reynolds, & Cambra, 1987). The typical methodology for most investigations is one in which the researcher manipulates a contrived message (i.e., blanked paragraph) by inserting words or phrases rated high or low in intensity and then evaluating the impact of the Randall G. Rogan (Ph.D. Michigan State University, 1990) is an Assistant Professor in the Department of Speech Communication at Wake Forest University.…”
Section: Randall G Roganmentioning
confidence: 99%
“…For example, in the fear appeals research, the same base message appears in the series of studies reported by Dabbs and Leventhal (1966), Leventhal, Jones, and Trembly (1966), Leventhal, Singer, and Jones (1965), and Rosen, Terry, and Leventhal (1982); in this research areaŝ everal other messages make repeat appearances in pairs or triplets of studies. Likewise, in the language intensity literature, the six studies reported in Burgoon and Chase (1973), Burgoon, Jones, and Stewart (1975, experiments 2 and 3), Burgoon and King (1974), and Chase and Kelly (1976, studies 1 and 2) appear to use a total of two base messages.…”
Section: The Empirical Evidence Of Message-by-treatment Interactionsmentioning
confidence: 99%